2012
DOI: 10.1186/1752-153x-6-66
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids, total polyphenols and antioxidant activity of grapes (Vitis vinifera) cultivated in organic and conventional systems

Abstract: BackgroundOrganic agriculture involve plants which are cultivated without using synthetic pesticides, herbicides or fertilizers and promotes biodiversity, biological cycles and improve the product quality. The carotenoids, total polyphenols and the antioxidant activity from skins of some wine and table grapes cultivated in organic and conventional agriculture were studied.ResultsThe main carotenoids identified using high performance liquid chromatography were lutein and ß-carotene. Muscat Ottonel variety has t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 42 publications
8
77
1
2
Order By: Relevance
“…In this study, grape skin showed higher scavenging activity compared to its pulp, and Flame seedless cultivar exhibited highest activity. Earlier studies had also shown that grape skin was good source of phenolics, had a high antioxidant capacity, and could be used as a potential source of natural antioxidants [36]. Significant correlation between the scavenging activities of grape extracts with phytochemicals, such as total phenolics and flavonoids, as observed in the current study, is in agreement with the previous studies [16,37,38].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, grape skin showed higher scavenging activity compared to its pulp, and Flame seedless cultivar exhibited highest activity. Earlier studies had also shown that grape skin was good source of phenolics, had a high antioxidant capacity, and could be used as a potential source of natural antioxidants [36]. Significant correlation between the scavenging activities of grape extracts with phytochemicals, such as total phenolics and flavonoids, as observed in the current study, is in agreement with the previous studies [16,37,38].…”
Section: Discussionsupporting
confidence: 92%
“…Grape pomaces skins of native French varieties also contain a very low TAC (Ky et al, 2014). These studies clearly show that the variety is really important in terms of TAC, but the difference between our result and those reported by previous research could also be related to the analytical methods involved (Bunea et al, 2012a). Higher values of TAC, compared to whole grape pomaces analyzed in other studies, were also found in mixed flours from 'Fetească neagră' (Corrales et al, 2008).…”
Section: Total Anthocyanins Content (Tac)contrasting
confidence: 51%
“…In the past few years, Romanian research has been concentrated more on polyphenols from fresh grapes or wines and very few on the quantity of compounds that remains in grape pomace with perspective of using it as raw material in other industries (Chedea et al, 2011;Hosu et al, 2011;Bunea et al, 2012a;Bunea et al, 2012b;Lung et al, 2013;Urcan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The radical scavenging activities of M. oleifera extract observed in this study were comparable with those reported by Sultana, Anwar, and Ashraf (2009) while that of B. pilosa extract were slightly lower than those reported by Adedapo et al (2011). Also, the presence of chlorophyll and carotenoid has been reported to contribute significantly to antioxidant activity of plant species through their ability to scavenging reactive oxygen species, singlet molecular oxygen and peroxyl radicals (Bunea et al, 2012). The chlorophyll a (2.62 ± 0.05 mg/g DW) and b (0.98 ± 0.01 mg/g DW) contents in B. pilosa were significantly higher (p < 0.05) than those of M. oleifera leaves (Table 4).…”
Section: Antioxidant Activities Of the Plant Extractsmentioning
confidence: 99%